Romanian Commitment to Independence of Justice and Anticorruption Reforms under CVM and Rule of Law Incentives. Some Considerations on Case-Law of the Constitutional Court - Cynthia Carmen Curt (Transylvanian Review of Administrative Sciences, 2022)
During 2017-2019 Romania faced a controversial justice laws’ ‘reform’, undermining the rule of law and independence of justice principles, challenging the commitments established under Commission Decision 2006/928/EC in the areas of judicial reform and the fight against corruption. In the context of democratic backsliding in Central and Eastern Europe, Romanian evolutions could be seen as following a regional pattern. The study proposes a critical analysis of the most important legislative evolutions in the area of justice and fight against corruption in the region, as reflected by the Cooperation and Verification Mechanism for Romania (CVM) and Rule of Law Reports, European Court of Justice and European Court of Human Rights judgements. The analysis focuses on some controversial decisions of the Constitutional Court, concerning justice laws ‘reform’ and the application of primacy of EU law principle. The study expresses a strong concern related to Romanian Constitutional Court’s tendencies to walk along the authoritarian path of politically captured courts of Poland and Hungary. The conclusions reveal the requirement for new political instruments of EU supranational intervention to safeguard democratic EU core values.